2017
DOI: 10.1097/iyc.0000000000000096
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Teachers' Use of Pyramid Model Practices in Mainland China

Abstract: The social domain is 1 of 5 preschool curricular domains in mainland China. Chinese preschool teachers are expected to use teaching practices that foster young children's social competence. The purpose of this study was to explore a small sample of Chinese preschool teachers' use of teaching and behavior support practices associated with the Pyramid Model. Twenty preschool classrooms in mainland China were observed using the prepublication version of the Teaching Pyramid Observation Tool for Preschool Classroo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
1
12
1
1
Order By: Relevance
“…Participating preschool teachers were observed to use approximately 14% of the Key Practices, and the level of preschool teachers' implementation did not vary significantly across classroom types and levels. In the absence of training and professional development, low levels of teachers' implementation of practices to support social-emotional competence were observed in other studies (e.g., Heo et al, 2014;Luo et al, 2017;Steed & Roach, 2017). However, in comparison to studies conducted in South Korea, China, and the United States, the levels of Turkish preschool teachers' use of practices to support young children's social-emotional competence were considerably low.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Participating preschool teachers were observed to use approximately 14% of the Key Practices, and the level of preschool teachers' implementation did not vary significantly across classroom types and levels. In the absence of training and professional development, low levels of teachers' implementation of practices to support social-emotional competence were observed in other studies (e.g., Heo et al, 2014;Luo et al, 2017;Steed & Roach, 2017). However, in comparison to studies conducted in South Korea, China, and the United States, the levels of Turkish preschool teachers' use of practices to support young children's social-emotional competence were considerably low.…”
Section: Discussionmentioning
confidence: 57%
“…A number of studies have demonstrated that children who have deficits in socialemotional development are more likely to demonstrate challenging behaviors (Dunlap et al, 2006;Hemmeter & Conroy, 2018;Luo, Snyder, Clark, & Hong, 2017;Webster-Stratton & Reid, 2004). Children who exhibit challenging behavior during preschool years are at risk for failure in formal schooling and their adult lives are often characterized by violence, anxiety, and abuse (Diken, Cavkaytar, Batu, Bozkurt, & Kurtyilmaz, 2010;Greenberg & Kusche, 2006;Overton, McKenzie, King, & Osbourne, 2002; Technical Assistance Center on Social Emotional Intervention for Young Children [TACSEI], 2004;Turan, Erbas, Yucesoy-Ozkan, & Ulke-Kurkcuoglu, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Özetle çocukların sosyal-duygusal açıdan sağlıklı gelişebilmeleri için okul öncesi öğretmenlerinin hem sınıflarında gözlemlenen problem davranışları doğru belirlemeleri hem de problem davranışlara müdahalede pedagojik açıdan uygun stratejileri kullanmaları önemlidir (Erbaş ve Yücesoy-Özkan, 2010;Öngören-Özdemir ve Tepeli, 2016;Uysal ve diğerleri, 2010). Dolayısıyla öğretmenlerin, problem davranışları belirlemeye, bu davranışların ortaya çıkmasını önlemeye ve problem davranışları ortadan kaldırmaya yönelik bilgi ve beceriye sahip olması gerekmektedir (Hemmeter ve diğerleri, 2016;Luo, Snyder, Clark ve Hong, 2017;Steed ve Roach, 2017). Yapılan araştırmalarda çoğunlukla okul öncesi öğretmenlerinin problem davranışlar ve müdahale yolları ile ilgili genel bilgileri görüşme yoluyla ölçülmüştür ve bulgular öğretmenlerin bu konuda bilgi eksikliklerinin olduğunu göstermiştir.…”
unclassified